On the way to a new corporate identity: dissertations in the early Soviet Period - Evgenii Rostovtsev; Ilya Sidorchuk (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The research is devoted to the defense of doctoral dissertations during the period of their legislative abolition – from 1918 to 1934. The authors focused on the question of the reasons for the preservation of protection rituals in new conditions, the peculiarities of their organization, the reasons for the gradual return to official practices of awarding degrees and, finally, the most important differences between the defense procedures of the 1930s and pre-revolutionary. The source base consisted of archival materials of a number of Soviet universities and academic institutions, as well as various egodocuments of representatives of the academic community and periodicals, which allowed reconstructing the protection procedure during the period under review. In addition, legislative sources regulating the procedure for preparation Soviet scientific personnel and, in particular, awarding academic degrees were actively involved. As a result, it is concluded that it may be more about the external similarity of the system of pre-revolutionary and Soviet protections. The awarding of degrees still played the role of an incentive for a scientific career, but a significant part of the powers associated with its regulation was withdrawn from the scientific community. The process of “pre-defense”, where the main decisions on the fate of the dissertation were still made, ceased to be exclusively a corporate matter of the professorial board. In addition, ideological control over the content of the dissertation research appeared. Another important difference was that the dissertation, in essence, became closed to the public, and the dispute largely lost the features of the theatrical performance that the university corporation gave to society in the previous period. As a result, the awarding of degrees turned from a corporate ritual that protected the academic autonomy of the scientific community in the pre-revolutionary period into a means of controlling it and an instrument of state policy. At the same time, this transformation was not complete, it was hindered by the very nature of science as a social practice, impossible in a situation of complete lack of autonomy.